Protein–protein interactions between triadin and calsequestrin are involved in modulation of sarcoplasmic reticulum calcium release in cardiac myocytes - Terentyev, Dmitry (Blackwell Science Inc, 2007)
In cardiac muscle, intracellular Ca(2+) release is controlled by a number of proteins including the ryanodine receptor (RyR2), calsequestrin (CASQ2), triadin-1 (Trd) and junctin (Jn) which form a complex in the junctional sarcoplasmic reticulum (SR) membrane. Within this complex, Trd appears to link CASQ2 to RyR2 although the functional significance of this interaction is unclear. In this study, we explored the functional importance of Trd–CASQ2 interactions for intracellular Ca(2+) handling in rat ventricular myocytes. A peptide encompassing the homologous CASQ2 binding domain of Trd (residues 206–230 in the rat; TrdPt) was expressed in the lumen of the SR to disrupt Trd–CASQ2 interactions. Myocytes expressing TrdPt exhibited increased responsiveness of SR Ca(2+) release to activation by I(Ca) as manifested by flattened and broadened voltage dependency of the amplitude of cytosolic Ca(2+) transients. Rhythmically paced, TrdPt-expressing myocytes exhibited spontaneous arrhythmogenic oscillations of intracellular Ca(2+) and membrane potential that was not seen in control cells. In addition, the frequency of spontaneous Ca(2+) sparks and Ca(2+) waves was significantly increased in TrdPt-expressing, permeabilized myocytes. These alterations in SR Ca(2+) release were accompanied by a significant decrease in basal free intra-SR[Ca(2+)] and total SR Ca(2+) content in TrdPt-expressing cells. At the same time a synthetic peptide corresponding to the CASQ2 binding domain of Trd produced no direct effects on the activity of single RyR2 channels incorporated into lipid bilayers while interfering with the ability of CASQ2 to inhibit the RyR2 channel. These results suggest that CASQ2 stabilizes SR Ca(2+) release by inhibiting the RyR2 channel through interaction with Trd. They also show that intracellular Ca(2+) cycling in the heart relies on coordinated interactions between proteins of the RyR2 channel complex and that disruption of these interactions may represent a molecular mechanism for cardiac disease.